Capital Structure: between Liquidity, Company Size, and Profitability - Imawan, Zidane; Tumirin (Universitas Sains dan Teknologi Komputer, 2024)
The increasing need for buildings and land has the effect of increasing construction in the housing sector. However, it must be understood that a company is able to regulate the structure of its funds. The maximum fund structure has an effect on the size of the fund and its value. This lesson will explain each variable raised as a study topic. This learning takes a quantitative approach through purposive sampling. The analysis uses classical assumption testing, descriptive statistics, as well as hypotheses using multiple linear regression methods using SPSS 25.0. The total study sample was 110 samples. Personally shows that the scale has a good effect on the fund structure. LiquidityProfitability is bad for the structure of funds. Then, together with the independent variables, they have a significant effect on the structure of the funds.